Analisis Persepsi Siswa Terhadap Lingkungan Sekolah Di SMA Swasta Santa Maria Medan - Tarigan, Rapina Maya Sari; Pardede, Sanggam; Siahaan, Mian (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
The phenomenon at Santa Maria Private High School in Medan shows that the school environment often faces challenges that can disrupt students’ learning, such as disruptions from traffic around the school, a lack of tranquility in the classroom, and limited use of learning facilities. These conditions can influence students’ perceptions of comfort, safety, and motivation to learn. This study aims to analyze students’ perceptions of the school environment at Santa Maria Private High School in Medan, encompassing physical, social, and academic aspects. The method used was a descriptive qualitative approach, with data collection techniques including interviews, observation, and documentation. The research informants consisted of nine tenth-grade students as key informants and five teachers as supporting informants, using a snowball sampling technique. The results showed that students generally had positive perceptions of the school environment, particularly regarding classroom comfort, cleanliness, security, and a conducive learning environment. However, students still experienced challenges, such as high levels of disruption, the need for improved discipline among some students, and limited use of learning facilities.